Four new Neotropical species of Episcepsis Butler, 1877 (Lepidoptera: Erebidae: Arctiinae) - Mantilla, Karla; Grados, Juan (Zootaxa, 2021)
The genus Episcepsis Butler, 1877 is widely distributed in the Neotropical region and currently includes 43 valid species many of them described solely based on external morphology. The existence of species complexes makes their identification difficult without examination of genital morphology. Four new species from Brazil, Cuba and Peru are described herein; Episcepsis andina sp. nov., E. diversa sp. nov., E. insularis sp. nov. and E. travassosi sp. nov. Comparisons with other similar species as well as photographs of external morphology and male genitalia are provided.